Exploring phoneme-grapheme connections in Malay word building. Issue 1 (2nd January 2019) - Lee, Lay Wah; Low, Hui Min; Lee, Sien Sut
ABSTRACT: As there is still debate on whether Ehri's phase theory of word development is relevant to more transparent orthographies, this investigation explores the alphabetic connections in the memory of early readers of Malay. A comparison design was applied with extreme groups as an independent variable. The extreme groups comprise of a sample of 32 high-performing and 24 low-performing Grade 2 students. A non-word building task with letter chunks of various grain-sizes measured decoding skills. The use of syllabic and multi-letter chunks to build non-words is evidence of unitisation of phoneme-grapheme connections in the students' memory. The results indicated that the high-performing students significantly unitised more than the low-performing students, using cues from the consolidated alphabetic phase. Moreover, error patterns indicated limited phoneme-grapheme connections among the low-performing students, evidence of partial alphabetic phase of development. However, comparisons within groups showed predominant use of letter chunks in both the high and the low-performing students which imply that both groups have advanced into the consolidated alphabetic phase. In conclusion, Ehri's phase theory is relevant for the transparent Malay language writing system; furthermore the transparency of the writing system may have facilitated the advancement of the less skilled readers into the consolidated alphabetic phase.